Influence of Geographical Area and Living Setting on Children's Weight Status, Motor Coordination, and Physical Activity - Gallotta, Maria Chiara; Zimatore, Giovanna; Falcioni, Lavinia; Migliaccio, Silvia; Lanza, Massimo; Schena, Federico; Biino, Valentina; Giuriato, Matteo; Bellafiore, Marianna; Palma, Antonio; Battaglia, Giuseppe; Baldari, Carlo; et al. (Frontiers in Pediatrics, 2022)
This study was aimed i) to examine the effect of living setting (rural vs urban), geographical area (North vs Centre vs South) and gender (boys vs girls) on weight status, motor coordination and physical activity (PA) level of Italian school-age children; ii) to examine differences on neighbourhood walkability of different school areas from different geographical areas and living settings; and iii) to examine whether motor coordination, PA level, geographical areas, living setting, neighborhood walkability and gender could predict children’s weight status. We assessed anthropometric parameters, gross motor coordination and PA level in 1549 children aged between 8 and 13 years. Results revealed that Central children had higher BMI than Northern and Southern children (ɳ2 = 0.01). Moreover, Northern children showed the highest motor quotient (ɳ2 = 0.148) and PA level (ɳ2 = 0.02), followed by Southern and Central children, respectively. Children from the South of Italy attended schools located in neighborhoods with the highest Walk Score®. Urban children attended schools located in neighborhoods with a higher Walk Score® than rural children. Lower motor quotient (MQ), lower PA level, living in rural setting and in a car-dependent neighborhood were associated with a higher relative risk for obesity. Being a girl was associated with a lower relative risk for obesity. The alarming high percentage of overweight and obesity in children as well as motor coordination impairments revealed the urgent need of targeted PA interventions in pediatric population.